Tuberculosis treatment outcomes: a fifteen-year retrospective study in Jos-North and Mangu, Plateau State, North - Central Nigeria - Comfort Nanbam Sariem; Patricia Odumosu; Maxwell Patrick Dapar; Jonah Musa; Luka Ibrahim; John Aguiyi (BMC, 2020)
Abstract Background Globally, tuberculosis (TB) is the leading cause of death from a single infectious agent. Adherence to TB therapy is an important factor in treatment outcomes, which is a critical indicator for evaluating TB treatment programs. This study assessed TB treatment outcomes using a fifteen-year record of tuberculosis patients who received treatment in Jos-North and Mangu Local Government Areas of Plateau State, North-Central Nigeria. Methods The retrospective facility based study was done in five TB treatment centers which account for more than half of data for tuberculosis patients in Plateau State. Data were collected from 10,156 TB patient's health records between 2001 and 2015. Treatment outcomes were categorized as successful (cured, treatment completed) or unsuccessful (non-adherent, treatment failure or death). A descriptive analysis was done to assess the factors associated with treatment outcomes. Relevant bivariate and multivariate logistic regression were done. All statistical analyses were performed on Stata version 11, College station, Texas, USA. Results During the study period, 58.1% (5904/10156) of the TB patients who received treatment were males. The Mean age ± SD was 35.5 ± 15.5 years. The overall treatment success rate was 67.4%; non-adherence/defaulting rate was 18.5%, with majority of patients defaulting at the end of intensive phase of treatment. The sputum conversion rate was 72.8% and mortality rate was 7.5%. A decrease in successful treatment outcomes rate from 83.8% in 2001 to 64.4% in 2015 was observed. The factors associated with treatment success were gender, age, year of enrollment, and HIV status. Extrapulmonary TB was less likely associated with treatment success (AOR:95% CI- 0.72:0.61-0.84, p < 0.001). Conclusion With the decrease in treatment success rates, underlying reasons for medication non-adherence and treatment failure should be resolved through adherence counseling involving the patient and treatment supporters, with education on voluntary counseling and testing for HIV among TB patients.